Association of urinary concentrations of early pregnancy phthalate metabolites and bisphenol A with length of gestation - Helen B. Chin; Anne Marie Jukic; Allen J. Wilcox; Clarice R. Weinberg; Kelly K. Ferguson; Antonia M. Calafat; D. Robert McConnaughey; Donna D. Baird (BMC, 2019)
Abstract Background Environmental exposure to phthalates and bisphenol A (BPA) may have endocrine disrupting effects that alter length of gestation. We assessed the association between the urinary concentrations of 11 phthalate metabolites and BPA with length of gestation in a cohort of women followed from before conception with daily 1st-morning urinary hormone measures that identified day of implantation. Methods Pre-implantation and post-implantation urinary phthalate metabolites and BPA concentrations were measured in pooled urine samples designed to limit single-measure variability due to the likely episodic nature of these exposures and the short half-life of these compounds. We estimated associations between these exposure biomarkers early in pregnancy with length of gestation from implantation to spontaneous birth. Cox proportional hazards models were used to estimate the hazard of birth among 125 naturally-conceived, singleton live births with censoring for medical interventions that artificially shortened pregnancy. Results Higher concentrations of mono (2-ethyl-5-hydroxyhexyl) phthalate (a metabolite of di (2-ethylhexyl) phthalate (DEHP)) during the pre-implantation window were associated with reduced probability of birth, i.e., longer gestations (hazard ratio (HR): 0.55, 95% CI: 0.35, 0.86; p = 0.01). The HR for the molar sum of the four DEHP metabolites measured showed a similar association (HR: 0.67, 95% CI: 0.43, 1.05). Higher concentrations of mono (3-carboxypropyl) phthalate (MCPP), a non-specific metabolite of several high molecular-weight phthalates, measured post-implantation were associated with increased risk of earlier birth, i.e. shorter length of gestation, HR: 1.59, CI: 1.02, 2.49. Conclusions Early gestational exposure to DEHP and possibly other high-molecular weight phthalates, (as reflected by urinary MCPP concentrations) may influence the length of pregnancy. Such effects could have consequences for neonatal and maternal health.